MEISSEN PORCELAIN IN UKRAINIAN COLLECTIONS. TERMINOLOGY AND PERIOD BREAKDOWN ISSUES - Решетньова, Г. О. (Art and Design, 2019)
The purpose of the suggested study are: to analyse and submit to public consideration the issue of correction of the Saxon porcelain terminology generally used in Ukraine; to analyse reasonableness of the dating principles applied to the ‘sculpture’ period of manufacturing; and to attribute and introduce into the academic turnover Meissen porcelain items kept in a Ukrainian private collection of D. Popov. The history & culture method and the context method have been applied to understand the role of Meissen porcelains in the global historic background. The modelling and abstraction methods helped understand the nature of 18 th century craftsmen’s work. Attribution of artworks has been accomplished through the arts expertise and comparative analyses. Results. Based on the study results, it has been found that the use of ‘chinoisrie’ term is not correct to designate Meissen porcelains manufactured in the first half of the 18 th century. Unavailability of the correct attribution of images in artworks of the said period prevents experts from using of the incorrect term. It is suggested to replace such term with a more comprehensive one – ‘orientalism’, which enables detailed identifying and description of artistic culture peculiarities in a certain country. In the context of this analysis, a cup and a plate manufactured in the first half of the 18 th century from a private Ukrainian collection have been introduced into the scientific turnover. Following the insight into craftsmen’s works and historic trends, it has been proved that the so-called ‘sculpture’ period of manufacturing requires reinterpretation. The examples cited in the Article imply that this stage should not be marked by certain dates, or the time interval should be extended taking into account the life period of a manufacturing founder. Consequently, in defiance of the conventional system, the Ukrainian expert community is becoming involved in reinterpretation of certain categories and processes in the decorative and applied arts. Scientific novelty of work involves terminology and dating revision, which is used by scientists towards Meissen porcelain manufactory of the first half of the XVIII century. The objects from private Meissen manufactory collection of D. Popov are used as a part of scientific research.